ANALISIS IMPLEMENTASI MODEL PEMBELAJARAN IPA DALAM MERDEKA BELAJAR DI SEKOLAH DASAR - Utari, Ni Kadek Sri; Abdullah, Gamar; Lasimpala, Aliya Ningsi; Pade, Amanda Erika; Uloli, Tri Mulyanny; Asmu, Anggie Libya Fatihah; Ayudia, Frizki (KNOWLEDGE: Jurnal Inovasi Hasil Penelitian dan Pengembangan, 2025)
This study examines the implementation of the Natural Sciences (IPA) learning model and the application of the Merdeka Belajar concept in class V of SDN 3 Kabila. The purpose of this study was to analyze the implementation of the IPA learning model, especially Project-Based Learning (PjBL), and its integration with the values ??in the Merdeka Belajar concept in class V students at SDN 3 Kabila. The method used in this study is a qualitative approach with a case study type carried out in class V of SDN 3 Kabila in the 2024/2025 academic year. Data collection in this study was carried out through semi-structured interviews with class V teachers and vice principals to obtain an overview of the implementation of science learning in the school. The results of the study show that the Project-Based Learning model is the main choice in science learning. This model is able to integrate the main values ??in the Pancasila Student Profile, such as critical and creative reasoning skills, independence, mutual cooperation, tolerance, and increased religiosity. The positive impact of the implementation of PjBL can be seen from the enthusiasm and activeness of students in participating in project-based learning. From the results of this study, it can be concluded that the implementation of the PjBL-based science learning model supports the concept of Independent Learning and contributes to improving the quality of science learning at SDN 3 Kabila. ABSTRAKPenelitian ini mengkaji implementasi model pembelajaran Ilmu Pengetahuan Alam (IPA) serta penerapan konsep Merdeka Belajar di kelas V SDN 3 Kabila. Tujuan dari penelitian ini adalah untuk menganalisis penerapan model pembelajaran IPA, khususnya Project-Based Learning (PjBL), serta integrasinya dengan nilai-nilai dalam konsep Merdeka Belajar pada siswa kelas V di SDN 3 Kabila. Metode yang digunakan dalam penelitian ini adalah pendekatan kualitatif dengan jenis studi kasus yang dilaksanakan di kelas V SDN 3 Kabila pada tahun ajaran 2024/2025. Pengumpulan data pada penelitian ini dilakukan melalui wawancara semi-terstruktur dengan guru kelas V dan wakil kepala sekolah untuk memperoleh gambaran implementasi pembelajaran IPA di sekolah tersebut. Hasil penelitian menunjukkan bahwa model Project-Based Learning menjadi pilihan utama dalam pembelajaran IPA. Model ini mampu mengintegrasikan nilai-nilai utama dalam Profil Pelajar Pancasila, seperti kemampuan bernalar kritis dan kreatif, kemandirian, gotong royong, sikap toleransi, serta peningkatan religiusitas. Dampak positif dari penerapan PjBL terlihat dari antusiasme dan keaktifan siswa dalam mengikuti pembelajaran berbasis proyek. Dari hasil penelitian ini dapat disimpulkan bahwa penerapan model pembelajaran IPA berbasis PjBL mendukung konsep Merdeka Belajar dan berkontribusi terhadap peningkatan kualitas pembelajaran IPA di SDN 3 Kabila.